Lugar e pertencimento: a cidade e o campo na percepção dos jovens da Comunidade Santa Luzia do Baixio, Iranduba, AM. - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
The aim of this dissertation was to understand the perceptions that young riverine dwellers in the interior of the state of Amazonas have of the surrounding urban and rural spaces. To reach this understanding we used semi-structured interviews with young people aged 15-25, based on the theoretical guidance of Phenomenology. Our goal was to identify the significance and the future projects that the young people in the Santa Luzia do Baixio Community attribute to these spaces, as well as reveal their feeling of belonging to the place they live. The place here is understood as the world of perceptions and experiences, comprehended through the subjectivity and culture. The Baixio is a riverine community, known mostly for maintaining their cultural values, based on cooperation and a close relationship with nature. We asked ourselves if there were modifications in their way of life resulting from the relationship with the city. We perceived that the youth are intimately linked to family ties and the culture that gave them their identity. However, their projects for the future include attending university, and migrating seems to be the only solution for those that see education as their only option for a better future.
Keywords: Cultura Ribeirinha; Percepção Cidade/Campo; Lugar e Pertencimento.; Riverine Culture; Rural/Urban Perception; Place and Belonging.; CIÊNCIAS HUMANAS: GEOGRAFIA